Longitudinal Associations Between Sleep and Needs Satisfaction on Mental Health Outcomes in Athletes - Stephen Shannon; Christopher Knowles; Noel Brick; Gavin Breslin (Journal of Clinical Sport Psychology, 2025)
Introduction : Sleep problems are linked to the occurrence and exacerbation of mental ill-being. Yet, scant research has been conducted in athletes and is hindered by a lack of theoretical grounding and mainly cross-sectional study designs. Method : Underpinned by self-determination theory, the present study incorporated a two-wave longitudinal design across a competitive sporting season. Three statistical models tested cross-lagged associations between needs satisfaction and sleep across adjacent time points, along with changes in mental health outcomes of depressive symptoms, anxiety symptoms, and well-being. Results : A total of 136 athletes took part ( M age : 29 years; 74% team sport athletes; 69% males). Early-season sleep difficulties led to poorer perceptions of midseason need satisfaction and indirectly impacted changes in all mental health outcomes through midseason needs satisfaction. Conclusions : Sleep difficulties are associated with poorer mental health outcomes in athletes, indirectly through needs satisfaction. Athlete sleep education interventions are recommended and could complement existing mental health programs.